Investment in the education of children in 16th century Poland - Izydorczyk-Kamler, Anna; Wyczański, Andrzej (Studia Historiae Oeconomicae, 2001)
Polish historiography has been interested for many years in the history of education considered, however as the history of schools as institutions. Simultaneously the problem of the pedagogical ideas and the model of upbringing of children was the goal of numerous studies. Quite recently some historians have observed the level of literacy in Poland of the 16th century. Nevertheless nobody has tried to approach this problem from the social and economic point of view; the study of the functioning of schools, namely of the investment and rentability of child education. This investment and rentability are not the problems of our economic calculation in the meaning of our quantified notion, but obviously that of the reasoning of the people living in the 16th century Poland.